Challenges and support factors of married Emirati students in teacher education - Stringer, P; Saqr, S; Tennant, L (Quest Journals Inc, 2014)
The United Arab Emirates (UAE) is on the path to becoming a knowledge economy and the role women play as pioneers and innovators, not only in their own society but, also, in the global community is strongly advocated [1]. Involvement of women in tertiary education and in the work force is promoted despite restrictions as to the kinds of jobs they can take up and difficulties associated with socio-cultural factors. When making career choices, teaching appears to be favored as a respectable, stable job involving limited interaction with the opposite sex. This paper explores the motivational factors, challenges and support strategies of a social group of married female Emirati students undertaking their Bachelor of Education (BEd.) teaching degree. Using Bronfenbrenner’s ecological systems theory [2] and socio-cultural influences on ‘self’ among the various nested systems that play a role in their development, data on motivational factors, challenges and support strategies are portrayed in the findings.
Keywords: Emirates; Teacher; Education; Married; Challenges